Effect of Mutans Streptococcal Colonization on Plaque Formation and Regrowth in Young Children – A Brief Communication - Christian Lee, DDS, MS; Norman Tinanoff, DDS, MS; Glenn Minah, DDS, PhD; (Blackwell Synergy, 2008)
Visible plaque on the maxillary anterior teeth of young children has been identified as a risk indicator for early childhood caries.